KAJIAN NUMERIK PENGARUH PROFIL SUDU TERHADAP KINERJA TURBIN HYDROKINETIC DARRIEUS SEBAGAI WAVE AND CURRENT ENERGY CONVERTER - Muchammad Fajar Muttafaq; Burniadi Moballa; George Endri Kusuma (Proceedings Conference on Marine Engineering and its Application, 2023)
New and Renewable Energy (EBT) resources in Indonesia are still not fully utilized,especially from the the maritime sector. Currently, the EBT mix has only reached 11.2 percent, stillbelow the 2025 energy mix target of 23 percent and the potential for EBT which reaches more than 400Gigawatts (GW) has only been utilized at 10 GW or 2.5 percent of the total reserves. (EBTKE PublicRelations, 2021). The form of wave and current energy is one of the new renewable energies from thesea which has the potential to be used as electrical energy with very large energy reserves. In this FinalProject research, a 2D modeling simulation based on CFD (Computational Fluid Dynamics) wascarried out on the Darrieus hydrokinetic turbine as an ocean wave energy converter device.Simulations were carried out to analyze the effect of the blade profile on the Torque Coefficient (Ct)and Power Coefficient (Cp) values. In this study, wave data from one of the South Java Waters wasused. The highest Coefficient of Torque (Ct) and Coefficient of Power (Cp) values were obtained forthe NACA 0021 symmetrical blade profile with a variation of TSR = 0.25 and ? = 0.5, namely Ct =0.335 and Cp = 0.167 while for the asymmetrical blade profile NACA 63-415 with a variation of TSR= 0.25 and ? = 5 for Ct = 0.263 and Cp = 0.132